2008
DOI: 10.1002/rcm.3814
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion source for chlorine isotope ratio measurements

Abstract: A negative chlorine ion source has been designed and constructed. The source utilizes direct surface ionization of chloromethane gas on a hot metal filament. Four different alloys for the filament material were tested: W99Th1, W75Re25, Hf97.5Zr2.5 and Mo52.5Re47.5. We conclude that the best filament material is the MoRe alloy, for which the signal-to-noise ratio is optimal. The ion source is used for chlorine isotope ratio measurements with higher precision and sensitivity than the positive ionization source u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The effects from polyatomic ion interferences that could not be removed completely were also considered. In the present study, ICP-MS/ MS in single-MS mode with H2 as collision reaction gas was not demonstrated because huge polyatomic ions of 36 …”
Section: Isotope Ratio Measurements Carried Out By Icp-ms/ms In Ms/ Mmentioning
confidence: 72%
See 3 more Smart Citations
“…The effects from polyatomic ion interferences that could not be removed completely were also considered. In the present study, ICP-MS/ MS in single-MS mode with H2 as collision reaction gas was not demonstrated because huge polyatomic ions of 36 …”
Section: Isotope Ratio Measurements Carried Out By Icp-ms/ms In Ms/ Mmentioning
confidence: 72%
“…Table 3 summarizes analytical sensitivities such as slope, blank, limits of detection (LODs, 3σ) and background equivalent concentration (BEC) observed for ICP-SFMS and ICP-MS/MS examined in the present study. The ICP-SFMS, ICP-MS/MS in MS/MS mode with H2 gas and ICP-MS/MS in single-MS mode without collision reaction gas showed similar values of slope and BEC for each Cl isotope, except for the BEC obtained by ICP-MS/MS in single-MS mode for 37 Cl which was attributed to the huge background signal from 36 Ar 1 H polyatomic ion interference. The lower LODs could be obtained by the ICP-MS/MS with H2 gas for both Cl isotopes as listed in Table 3.…”
Section: CLmentioning
confidence: 77%
See 2 more Smart Citations
“…This is a reason why thermal ionization mass spectrometry (TIMS) is a convenient method for the precise measurement of Li and K isotope ratios. The TIMS method can also be applied to the ionization of several other compounds and atoms in both, positive and negative modes …”
Section: Introductionmentioning
confidence: 99%